DIAGNOSIS AND MANAGEMENT CHRONIC INSOMNIA - Puspitha Candra, G.A Dian (E-Jurnal Medika Udayana; vol 2 no3 (2013):e-jurnal medika udayana)
Insomnia is defined as difficulty to start sleeping, maintain it, or low quality sleeping, if the condition persist for more than one month, it is called chronic insomnia. Diagnosis is made through anamnesa and sleep wake diaries, aktigraphy, polisomnography. Pharmachologycally drugs that have been used to treat insomnia are benzodiazepin reseptor agonis, antihistamine, antidepressant. Non pharmacological ways include behavioural intervention for insomnia, give significant result in decreasing sleep latency, reducing awakness duration during the night and improving total sleeping time.
Keywords: chronic insomnia, behavioural intervention